Assessment of the cobas® HBV RNA investigational assay in the setting of nucleoside analog therapy cessation. Issue 12 (30th August 2022) - Jackson, Kathy; Bonanzinga, Sara; Edwards, Ros; Visvanathan, Kumar; Li, Xin; Hall, Samuel; Kuchta, Alison; Canchola, Jesse A.; Thompson, Alex J.
Abstract: HBV RNA is used as a marker of cccDNA transcription and is applicable in the setting of nucleos(t)ide analog (NA) treatment, which suppresses HBV DNA. Traditional assays for quantification of HBV RNA rely on labor‐intensive 3′RACE assays targeting the polyA tail. In this study, the high‐throughput Roche cobas®HBV RNA investigational assay was assessed on the Roche cobas® 6800 automated platform. Of 969 samples collected for a NA treatment cessation trial, and tested on the cobas assay, 249 were analyzed for sensitivity, reproducibility, sample type applicability, and results were compared to a RACE‐based assay. Results of 97 paired serum and plasma samples demonstrated an excellent correlation of 0.98. However, 14.5% of plasma samples yielded detectable (below the limit of quantification) results, when the paired serum was undetectable, and plasma was shown to yield a statistically significant ( p  < 0.001) greater mean 0.119 log10 copies/ml. Quantification of 152 samples showed good correlation (0.91) between the cobas and RACE assays. The cobas assay demonstrated superior lower limit of quantification, 10 copies/ml, which resulted in detection of 13.2% more samples than the RACE assay. Reproducibility and linear range of the automated assay were also confirmed. The Roche cobas assay for HBV RNA is sensitive and highly recommended.